Estimating treatment effect of tafamidis on hospitalisation in NYHA class III ATTR-CM patients in the presence of death using principal stratification. (14th October 2021) - Li, H; Rozenbaum, M.H; Casey, M; Sultan, M
Abstract: Background: Hospitalisation has been widely used as a measure of morbidity in clinical trials for chronic heart failure. As previously reported in the Transthyretin Amyloidosis Cardiomyopathy Clinical Trial (ATTR-ACT), the observed frequency of cardiovascular (CV)-related hospitalisations favoured tafamidis over placebo in all analyses except in the NYHA Class III baseline subgroup with a relative risk of 1.41 [95% CI: 1.05, 1.90]1. However, the evaluation of the causal effect of treatment on hospitalisation is complicated in the presence of death as death precludes further hospitalisation and thus limits the evaluation of hospitalisation rates between groups. This confounding effect of death is particularly relevant in NYHA Class III participants who had higher mortality rates compared to Class I or II participants. Purpose: This aim of this study was to assess the impact of the confounding effect of death on CV-related hospitalisation. Methods: The effect of tafamidis treatment on CV-related hospitalisations was defined and compared in the subset of participants from either treatment arm who were alive at the end of the study (ie, Month 30); however the subset of participants who survive on the tafamidis arm would be expected to have different characteristics from the subset of participants who survive on the control arm and thus these analyses do not estimate the causal effect. To address this possible survivor bias, we additionally conducted a post hoc principal stratification analysis. Principal stratification is a statistical method to adjust for post treatment events, in this case mortality, by classifying participants according to their potential to survive under each treatment arm. Specifically, we sought to estimate the principal strata effect on CV-related hospitalisations in NYHA Class III participants who would survive irrespective of treatment assignment. Sensitivity analyses were performed to assess the model assumptions. Results: The analysis within the subset of participants who survived at Month 30 demonstrated a relative risk of 1.1 (95% CI: 0.56, 2.16) between tafamidis and placebo. The principal stratification analyses of subjects who would survive to 30 months irrespective of treatment estimated a 0.75 (95% CI: 0.44, 1.23) relative risk between tafamidis and placebo, suggesting a 25% reduction in frequency of CV-related hospitalisations in the tafamidis arm. Conclusion: The initial data reported in ATTR-ACT likely underestimated the true effect of tafamidis on CV-related hospitalisations due to the confounding effect of death. The analysis of treatment group among observed survivors estimated a smaller relative risk for NYHA Class III; however, this analysis does not fully address the possible survivor bias. The survivor average causal effect, which adjusts for the survival bias demonstrated a reduction in the frequency of CV-related hospitalisation in the tafamidis treated arm for NYHA Class III participants. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pfizer